Ultrastructural study of the hypothalamus in mice chronically treated with manganese - Villalobos, Virginia; Martínez, Juan Carlos; Castellano, Alan; Hernández Fonseca, Juan Pablo; Medina Leendertz, Shirley; Bonilla, Ernesto (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Manganese (Mn) is an essential metal that is an integral part of some metalloproteins and acts as a cofactor of several enzymes. Mn is able to cross the blood-brain barrier and enter the nervous system. It has a low toxicity but exposure to high concentrations or for prolonged periods of time produce neurological disorders in humans that initially cause hallucinations and compulsive behaviour followed by stiffness, muscle weakness, ataxia, memory loss and a tremor resembling Parkinson”™s disease. This study assessed the ultrastructural alterations produced in the hypothalamus of male albino mice injected intraperitoneally with MnCl2 (5 mg Mn/Kg/day) and a control group injected with NaCl 0.9% (0.1 mL) daily for 9 weeks. The animals were sacrificed by cervical dislocation. The hypothalamus was extracted and subsequently processed to be observed on the conventional transmission electron microscope at 2, 4, 6 and 9 weeks of treatment. After 2 weeks it was observed a slight disruption of the Golgi apparatus and the myelin fibers. After 4 weeks the disorganization was accentuated and dilatation of the endoplasmic reticulum (ER) and alterations of mitochondria were observed. After 6 weeks the normal pattern of the myelin sheath was lost. After 9 weeks of treatment it was found swollen mitochondria with lost of crystae, a marked dilatation of rough and smooth endoplasmic reticulum and dendrites with a high degree of swelling. These results suggest that the neurotoxic effect of Mn increases as time of exposure passes and produces ultrastructural alterations of nerve cells in the hypothalamus.